Pendidikan Orang Dewasa (Andragogy) - Jauhan Budiwan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2018)
The purpose of writing this article are: 1) Understanding the understanding and concepts of science underlying adult learning; 2) Knowing the history anddevelopment of andragogy; 3) Understanding the implementation of adult education (Andragogy) which includes adult learning needs, adult educationprinciples, adult learning conditions, the effect of decreased adult physical factors, adult education methods, the implications for adult learning, and theadvantages. By using the theory of andragogy of adult learning activities or activities within the framework of development or realization of theachievement of lifelong educational ideals can be obtained with the support of theoretical concepts or the use of technology that can be justified. thedisadvantage is that how can a student who is not very knowledgeable about the extent of knowledge and then freed choose what they like? As if theAndragogy system was just as a system that only encouraged its students and forgot for what purpose it really was. Andragogy helps others to grow andmature. In Andragogy, the involvement of adults in the learning process is much greater, because from the beginning must be held a diagnosis of needs,formulate goals, and evaluate learning outcomes and implement them together.